1987
DOI: 10.1111/j.1469-8137.1987.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

WATER STRESS MODIFIES INTRASPECIFIC INTERFERENCE BETWEEN RUST (PUCCINIA LAGENOPHORAE COOKE)‐INFECTED AND HEALTHY GROUNDSEL (SENECIO VULGARIS L.)

Abstract: SUMMARYPopulations of groundsel {Senecio vulgaris L.) were grown in the field in bottomless containers which allowed roots to penetrate freely into the natural soil profile. The 36 plants within each population (equivalent to 1250 vcC"^) were either all inoculated with the rust Puccinia lagenophorae Cooke, all rust free, or were a 1:1 mixture of the two. Rain was excluded from all populations by small shelters. Half the populations were subjected to mild drought, whilst remaining populations were well-watered.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
(26 reference statements)
2
6
0
Order By: Relevance
“…Rust infection directly affected the competitive ability of the host beyond the effects of infection on plant growth. Similar effects of rust infection have been found for intraspecific competition, including between infected and noninfected groundsel (175) and between susceptible and resistant skeletonweed (Chondrilla juncea, Asteraceae) (51). Research of this sort is sorely needed outside of agroecosystems.…”
Section: Competition Succession and Plant Diversitysupporting
confidence: 55%
See 1 more Smart Citation
“…Rust infection directly affected the competitive ability of the host beyond the effects of infection on plant growth. Similar effects of rust infection have been found for intraspecific competition, including between infected and noninfected groundsel (175) and between susceptible and resistant skeletonweed (Chondrilla juncea, Asteraceae) (51). Research of this sort is sorely needed outside of agroecosystems.…”
Section: Competition Succession and Plant Diversitysupporting
confidence: 55%
“…Specialist pathogens like rusts can affect the competitive interactions between susceptible and nonsusceptible plant species or genotypes. Paul & Ayres found that inoculation of groundsel (Senecio vulgaris, Asteraceae) with the rust Puccinia lagenophorae significantly reduced groundsel growth, and reduced the competitive ability of groundsel with both lettuce (Lactuca sativa) (175) and the co-occurring weed petty spurge (Euphorbia peplus, Euphorbiaceae) (174). Rust infection directly affected the competitive ability of the host beyond the effects of infection on plant growth.…”
Section: Competition Succession and Plant Diversitymentioning
confidence: 99%
“…include host plants in well-watered conditions (Paul and Ayres 1987) and soils low in nitrogen (Paul 1989).…”
Section: Common Rust Severitymentioning
confidence: 99%
“…(1984). The method has particular value in separating and describing the magnitude of intra‐ and inter‐specific interference and has been used extensively in previous studies examining the impact of pathogens on plant interference (Paul and Ayres, 1987a,b; Paul, 1989). The magnitude of intra‐specific interference was determined as the relative monoculture response ( R m ): where Y p is the total projected yield in the absence of interference (calculated from the initial slope of the yield density curve) and Y m is the measured monoculture yield.…”
Section: Methodsmentioning
confidence: 99%